Odpowiedzi

2010-01-11T18:00:24+01:00
C) 2x + y = 9/ * -5 2x+y=9/ *4
5x - 4y = 3/ * 2 5x-4y=3/*1

-10x-5y=-45 8x+4y=36
10x-8y=6 5x-4y=3

-13y= -39/ : -13 13x= 39/:13
y=3 x=13

d) 3x - 2y = 5/*-2 3x-2y=5/*1
2x - y = 4/*3 2x-y = 2/*-2

-6x+4y= -10 3x-2y=5
6x-3y=12 -4x+2y=-4

y=2 -1y=1 /: -1
y=-1

e) 2x + 9y = -9/*3 2x + 9y = -9/*-3
-3x + 3y = 8/*2 -3x+3y=8/*9

6x+27y=-27 -6x-27=27
-6x+6y=16 -27x+27y=72

33y= -11 -33x=99 / :-33
x=-3

f) 2x + 3y = 4/*-8 2x+3y=4/*5
8x - 5y = -1/*2 8x-5y=-1/*3

-16x-24y=-32 10x+15y=20
16x-10y=-2 24x-15y=-3

-34y=-34/:-34 34x=17
y=1